2018
DOI: 10.1101/484212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rootstock effects on scion phenotypes in a ‘Chambourcin’ experimental vineyard

Abstract: 30Understanding how root systems modulate shoot system phenotypes is a fundamental question in 31 plant biology and will be useful in developing resilient agricultural crops. Grafting is a common 32 horticultural practice that joins the roots (rootstock) of one plant to the shoot (scion) of another, 33 providing an excellent method for investigating how these two organ systems affect each other. 34 65 66Grapevine (Vitis L. spp.) is an excellent model for examining rootstock-scion interactions due to 67 the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Previous research in this experimental vineyard from prior years, have shown that irrigation treatments have impacted multiple phenotypes, including, physiologic measurements in 2014-2015 (Maimaitiyiming et al . 2017) and the ionome and morphology of leaves in 2014-2016 (Migicovsky et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in this experimental vineyard from prior years, have shown that irrigation treatments have impacted multiple phenotypes, including, physiologic measurements in 2014-2015 (Maimaitiyiming et al . 2017) and the ionome and morphology of leaves in 2014-2016 (Migicovsky et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…2015; Gautier et al . 2020), shoot gene expression (Cookson and Ollat 2013), and leaf morphology (Migicovsky et al . 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many grapevine breeders employ grafting, a surgical enhancement that joins the aboveground portion of one plant (scion) to the root system of another individual (rootstock). Previous research has shown that both the environment and the rootstock have important effects on the phenotype of the grapevine scion (Dal Santo et al, 2013;Anesi et al, 2015;Chitwood et al, 2016b;Young et al, 2016;Migicovsky et al, 2019), and both have consequences for a wine's terroir (the concept that a wine's flavor is of a place, derived from a specific set of environmental, soil and microbial conditions that produce stark, but consistent flavor differences between clonally propagated cultivars grown in different regions) (Sabon et al, 2002). Furthermore, prior work also indicated that different clonal lineages of the wine grape cultivar Pinot noir can be distinguished by MSAP profiles (Ocaña et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…may preferentially partition ion contents to nearby seeds [74] . Position of inflorescences along a plant's stem has been shown to impact nutrient allocation in soybean seeds [30] and grapevine leaves [28] . Future work is needed to comprehensively sample Phaseolus seeds from throughout the plant in order to determine the effect of seed position on nutrient concentrations in this genus.…”
Section: Comparisons Of Ion and Amino Acid Concentrations In Annual Amentioning
confidence: 99%
“…In considering the development of crops for agricultural systems such as agroforestry, attention is focusing on species that provide high nutritional content [7], [9] as well as ecological functionality. Mineral and amino acid concentrations of plant species are influenced by both genetic and environmental factors [17]- [28] . In the common bean, Phaseolus vulgaris , uptake of iron, zinc, and amino acids varied across genotypes [18], [20] .…”
Section: Introductionmentioning
confidence: 99%